Partition this integral!

Calculus Level 2

1 2 x { x } { x } 2 x 2 x 2 d x \large \int_{1}^{\infty} \dfrac {2x\{x\} - \{x\}^2} {x^2 \lfloor x \rfloor ^2} \, dx

If the integral above can be expressed as π a b c \dfrac{\pi^a - b} c , where a , b , c a,b,c are all positive integers, find a + b + c a+b+c .

Notations:


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Chew-Seong Cheong
Dec 11, 2016

Relevant wiki: Riemann Zeta Function

I = 1 2 x { x } { x } 2 x 2 x 2 d x Note that { x } = x x = k = 1 k k + 1 2 x ( x k ) ( x k ) 2 k 2 x 2 d x = k = 1 k k + 1 2 x 2 2 k x x 2 + 2 k x k 2 k 2 x 2 d x = k = 1 k k + 1 x 2 k 2 k 2 x 2 d x = k = 1 k k + 1 ( 1 k 2 1 x 2 ) d x = k = 1 [ x k 2 + 1 x ] k k + 1 = k = 1 ( k + 1 k k 2 + 1 k + 1 1 k ) = k = 1 ( 1 k 2 + 1 k + 1 1 k ) Note that k = 1 1 k 2 = ζ ( 2 ) = π 2 6 = ζ ( 2 ) 1 1 where ζ ( ) denotes the Riemann zeta function. = π 2 6 1 = π 2 6 6 \begin{aligned} I & = \int_1^\infty \frac {2x \{x\} - \{x\}^2}{x^2\lfloor x \rfloor^2} dx & \small \color{#3D99F6} \text{Note that } \{x\} = x - \lfloor x \rfloor \\ & = \sum_{k=1}^\infty \int_k^{k+1} \frac {2x(x-k)-(x-k)^2}{k^2x^2} dx \\ & = \sum_{k=1}^\infty \int_k^{k+1} \frac {2x^2-2kx-x^2+2kx -k^2} {k^2x^2} dx \\ & = \sum_{k=1}^\infty \int_k^{k+1} \frac {x^2 - k^2} {k^2x^2} dx \\ & = \sum_{k=1}^\infty \int_k^{k+1} \left(\frac 1{k^2} - \frac 1{x^2} \right) dx \\ & = \sum_{k=1}^\infty \left[\frac x{k^2} + \frac 1x \right]_k^{k+1} \\ & = \sum_{k=1}^\infty \left(\frac {k+1-k}{k^2} + \frac 1{k+1} - \frac 1k \right)\\ & = \sum_{k=1}^\infty \left(\frac 1{k^2} + \frac 1{k+1} - \frac 1k \right) & \small \color{#3D99F6} \text{Note that }\sum_{k=1}^\infty \frac 1{k^2} = \zeta (2) = \frac {\pi^2}6 \\ & = \zeta(2) - \frac 11 & \small \color{#3D99F6} \text{where } \zeta(\cdot) \text{ denotes the Riemann zeta function.} \\ & = \frac {\pi^2}6 - 1 \\ & = \frac {\pi^2 - 6}6 \end{aligned}

a + b + c = 2 + 6 + 6 = 14 \implies a+b+c = 2+6+6 = \boxed{14}

I do not understand what you have done after the last summation.. somefunction(2) = pi square/6. Could you pls explain what that function is and how you got that sum as pi square/6?

Jaya Krishna - 3 years, 7 months ago

Log in to reply

I have added some explanation and a reference. Hope it is helpful. It is in fact the Basel problem that was first solved by Leonhard Euler .

Chew-Seong Cheong - 3 years, 7 months ago
Subh Mandal
Dec 10, 2016

how did u got integration of 1/[x]^2 from 0 to infinity ?

A Former Brilliant Member - 4 years, 4 months ago

Log in to reply

1 1 [ x ] 2 d x = n = 1 n n + 1 1 [ x ] 2 d x = n = 1 n n + 1 1 n 2 d x = n = 1 1 n 2 = π 6 \displaystyle\intop^\infty_1\!\!\!\dfrac{1}{[x]^2}\mathrm{d}x=\displaystyle\sum_{n=1}^\infty\intop^{n+1}_n\!\!\!\dfrac{1}{[x]^2}\mathrm{d}x=\displaystyle\sum_{n=1}^\infty\intop^{n+1}_n\!\!\!\dfrac{1}{n^2}\mathrm{d}x=\displaystyle\sum_{n=1}^\infty\dfrac{1}{n^2}=\dfrac{\pi}{6} .

Laurent Shorts - 4 years, 3 months ago

It's the value of reimann zeta function for s=2

Aanjaneya Pandey - 6 months, 2 weeks ago

nice one

incomplete steps

Shubham Rustagi - 4 years, 6 months ago

I did the same way.

Vraj Mistry - 4 years, 5 months ago
Anubhav Tyagi
Dec 20, 2016

2 x { x } { x } 2 x 2 x 2 = { x } ( 2 x { x } ) x 2 x 2 = { x } ( x + ( x { x } ) ) x 2 x 2 = ( x x ) ( x + x ) x 2 x 2 = x 2 x 2 x 2 x 2 = 1 x 2 1 x 2 Hence we evaluate the integral as = 1 1 x 2 d x 1 1 x 2 d x = ( 1 2 1 1 2 d x + 2 3 1 2 2 d x ) 1 1 x 2 d x = ( 1 1 2 + 1 2 2 + 1 3 2 ) 1 = π 2 6 1 = π 2 6 6 \begin{aligned} &\dfrac {2x\{x\} - \{x\}^2} {x^2 \lfloor x \rfloor ^2}=\dfrac{\{x\}\big( 2x - \{x\}\big)} {x^2 \lfloor x \rfloor ^2}=\dfrac{\{x\}\big( x+\big(x - \{x\}\big)\big)} {x^2 \lfloor x \rfloor ^2}=\dfrac{\big(x- \lfloor x \rfloor\big)\big( x+ \lfloor x \rfloor\big)} {x^2 \lfloor x \rfloor ^2}=\dfrac{x^2- \lfloor x \rfloor ^2} {x^2 \lfloor x \rfloor ^2}=\frac{1}{\lfloor x \rfloor ^2}- \frac{1}{x^2}\\ &\text{Hence we evaluate the integral as }\\ &=\displaystyle \int_{1}^{\infty} \frac{1}{\lfloor x \rfloor ^2} \,dx - \displaystyle \int_{1}^{\infty} \frac{1}{x^2} \,dx \\ &= \bigg(\displaystyle \int_{1}^{2}\frac{1}{1^2} \,dx +\displaystyle \int_{2}^{3}\frac{1}{2^2}\,dx \cdots \cdots \bigg) - \displaystyle \int_{1}^{\infty} \frac{1}{x^2} \,dx \\ &=\bigg(\frac{1}{1^2} + \frac{1}{2^2} + \frac{1}{3^2} \cdots \cdots \bigg) - 1 \\ &= \frac{\pi ^2}{6} -1 = \frac{\pi^2-6}{6} \\ \end{aligned}

Paul Hindess
Dec 10, 2016

Enjoyed this problem. Having never solved an integral involving either { x } \{x\} or [ x ] [x] , my approach is probably naive, but thought I would upload it for three reasons:

  1. as a Latex challenge for myself
  2. as a challenge to the reader (can anyone follow my thought process?!)
  3. to see if anyone else took a similar approach!

Here goes:

1 2 x { x } { x } 2 x 2 [ x ] 2 d x = n = 1 n n + 1 2 x { x } { x } 2 x 2 [ x ] 2 d x = n = 1 0 1 2 ( x + n ) x x 2 ( x + n ) 2 n 2 d x = n = 1 1 n 2 0 1 x 2 + 2 n x x 2 + 2 n x + n 2 d x = n = 1 1 n 2 0 1 1 n 2 x 2 + 2 n x + n 2 d x = n = 1 1 n 2 0 1 1 n 2 ( x + n ) 2 d x = n = 1 1 n 2 [ x + n 2 x + n ] 0 1 = n = 1 1 n 2 ( 1 + n 2 n + 1 0 n 2 n ) = n = 1 1 n 2 ( n + 1 ) \begin{aligned} \displaystyle \int_{1}^{\infty} \frac {2x\{x\} - \{x\}^2} {x^2[x]^2} dx & = \sum_{n=1}^{\infty} \int_{n}^{n+1} \frac {2x\{x\} - \{x\}^2} {x^2[x]^2} dx \\ & = \sum_{n=1}^{\infty} \int_{0}^{1} \frac {2(x+n)x - x^2} {(x+n)^2n^2} dx \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2} \int_{0}^{1} \frac {x^2+2nx} {x^2 + 2nx + n^2} dx \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2} \int_{0}^{1} 1- \frac {n^2} {x^2 + 2nx + n^2} dx \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2} \int_{0}^{1} 1- n^2(x+n)^{-2} dx \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2} \Big[x + \frac {n^2} {x+n}\Big]_0^1 \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2} \Big(1 + \frac {n^2} {n+1} - 0 - \frac {n^2} {n} \Big) \\ & = \sum_{n=1}^{\infty} \frac {1}{n^2(n+1)} \end{aligned}

And at this point I resorted to Wolfram Alpha because I was in too much of a hurry to check if my approach had been error-free and successful.

This gave me:

π 2 6 6 \frac {\pi^2 - 6}{6}

So a + b + c = 2 + 6 + 6 = 14 a+b+c= 2+6 + 6 = 14 .

Thanks for reading and well done if you followed even some of it! If anyone can suggest a non-Wolfram approach to the final integral, I'd be grateful.

Very neat solution! You might enjoy reading this article .

But, can you justify the interchanging of the summation and the integral in the first? Hint: Fubini's theorem.

For the final sum, you can break it up via partial fraction decompositions , to get

n = 1 1 n 2 ( n + 1 ) = n = 1 ( 1 n 2 + 1 n + 1 1 n ) = n = 1 1 n 2 = ζ ( 2 ) = π 2 / 6 + n = 1 ( 1 n + 1 1 n ) = 1 = π 2 6 6 , \sum_{n=1}^\infty \dfrac1{n^2 (n+1)} = \sum_{n=1}^\infty \left( \dfrac1{n^2} + \dfrac1{n+1} - \dfrac1n \right) = \underbrace{ \sum_{n=1}^\infty \dfrac1{n^2} }_{=\zeta(2) = \pi^2/6}+ \underbrace{\sum_{n=1}^\infty \left( \dfrac1{n+1} - \dfrac1n \right) }_{=-1} = \dfrac{\pi^2-6}6 ,

where the latter sum can be expressed as a telescoping series , n = 1 ( a n + 1 a n ) = lim N n = 1 N ( a n + 1 a n ) = lim N ( a N + 1 a 1 ) = 0 1 = 1. \displaystyle \sum_{n=1}^\infty (a_{n+1} - a_n) = \lim_{N\to\infty} \sum_{n=1}^N (a_{n+1} - a_n) = \lim_{N\to\infty} (a_{N+1} - a_1) = 0-1 = -1 .

Pi Han Goh - 4 years, 6 months ago

Log in to reply

Thank you. Should have thought have partial fractions! (-:

Paul Hindess - 4 years, 6 months ago

Yeah at first i kept thinking how to do it, but suddenly it struck me to do so by creating a general term for nth integral and then applying summation.

Raunak Agrawal - 4 years, 3 months ago

(Oh just realized Pi Han made a similar remark, so ignore.)

If by "final integral" you actually mean "final summation", then observe that by Partial Fractions ,

1 n 2 ( n + 1 ) = 1 n 2 + 1 n + 1 1 n . \frac{ 1 } { n^2 ( n+1 ) } = \frac{ 1}{ n^2 } + \frac{1}{n+1} - \frac { 1 } { n }.

Hence by the telescoping approach, the sum is ( 1 n 2 ) 1 \left ( \sum \frac{1}{n^2 } \right) - 1 .

Calvin Lin Staff - 4 years, 6 months ago

Log in to reply

Thanks! Very helpful. And, yes - I've changed it to read "final summation". (-:

Paul Hindess - 4 years, 6 months ago
Kushal Bose
Dec 12, 2016

1 2 x { x } { x } 2 x 2 [ x ] 2 d x \displaystyle \int_{1}^{\infty} \dfrac{2x\{x\}-\{x\}^2}{x^2 [x]^2 } dx

= 1 ( 2 x { x } ) { x } x 2 [ x ] 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{(2x-\{x\}) \{x\}}{x^2 [x]^2} dx

= 1 ( x + x { x } ) { x } x 2 [ x ] 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{(x+ x-\{x\}) \{x\}}{x^2 [x]^2} dx

= 1 ( x + [ x ] ) { x } x 2 [ x ] 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{(x+[x]) \{x\}}{x^2 [x]^2} dx

= 1 ( x + [ x ] ) ( x [ x ] ) x 2 [ x ] 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{(x+[x])(x-[x])}{x^2 [x]^2} dx

= 1 x 2 [ x ] 2 x 2 [ x ] 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{x^2-[x]^2}{x^2 [x]^2} dx

= 1 1 [ x ] 2 1 x 2 d x =\displaystyle \int _{1}^{\infty} \dfrac{1}{[x]^2} - \dfrac{1}{x^2} dx

Then it is a easy form .First part will give π 2 6 \frac{\pi^2}{6} and second part will give 1 -1

Can you explain how the 1st part gives pi square by 6

Nithin S - 8 months, 1 week ago
Bostang Palaguna
Dec 27, 2020

The idea is: We don't want to deal with { x } \{x\} so we utilize : { x } = x x \{x\} = x - \left \lfloor{x}\right \rfloor

by doing some algebra, we would get: 1 x 2 x 2 x 2 x 2 \int_1^\infty \frac{x^2 - \left \lfloor{x}\right \rfloor ^2}{x^2 \left \lfloor{x}\right \rfloor ^2}

make it up into two integral:

1 1 / x 2 d x \int_1^\infty 1/\left \lfloor{x}\right \rfloor ^2 dx and 1 1 / x 2 d x \int_1^\infty 1/x^2 dx

the second part is easy.

for the first part, imagine it in terms of area, you would have blocks with height of 1, 1/4, 1/9, 1/16, 1/25, ... and width of 1.

This is famously equal to π 2 / 6 \pi ^2 /6 (read : Riemann zeta function)

thus the integral result will be π 2 / 6 1 \pi ^2 /6 -1 .

a + b + c = 14 \therefore a + b + c = \boxed{14}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...